ASPEK KODIKOLOGIS DAN FILOLOGIS MANUSKRIP TAFSIR PONDOK PESANTREN BUSTANUL ULUM SEDAN REMBANG - Ma'ali, Nasichatul; Asif, Muhammad (AL ITQAN: Jurnal Studi Al-Qur'an, 2020)
This paper examines the collection of manuscript of Tafsir Jalālayn in the Pondok Pesantren Bustanul Ulum, Sedan District, Rembang, by focusing on textological and codicological aspects. This study is crucial to do to view the characteristic form of the text contained in the ancient manuscript of tafsir Jalālayn which then led to findings on how the Quranic interpretation was studied at that time. This research is a qualitative research with a codicology and textology (philology) approach. This finding strengthens the argument that the study of tafsir, especially Jalālayn, was introduced in the Rembang area in the first half of the 19th century, so that it can revise the findings of Van der Chijs and Van den Berg about the absence of tafsir teaching in Rembang area throughout the 19th century. This study identifies several characteristics found in the manuscript text. First, the use of the interlinear translation (Makna Gandhul) and its Javanese codes helps the students to understand the contents of Jalālayn's Arabic interpretation. Second, the hierarchy of language contained in its translation as a form of reflection of the reader's culture in the Javanese environment. Third, the existence of marginal notes written in Arabic indicates that attempts to comment on Jalālayn had been made earlier in the area. Another interesting finding is the consistent and fairly well-established use of codes in Arabic grammatical analysis, which is an indication that Makna Gandhul had evolved in that century.